2017
DOI: 10.1007/s40789-017-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigate the kinetics of coke solution loss reaction with an alkali metal as a catalyst based on the improved genetic algorithm

Abstract: The kinetics of coke solution loss reaction with and without sodium carbonate were investigated under the reaction atmosphere of carbon dioxide. The variables of gas flow rate and coke particle size were explored to eliminate the external and internal diffusion, respectively. Then, the improved method combining with the least square and the genetic algorithm was proposed to solve the homogeneous model and the shrinking core model. It was found that the improved genetic algorithm method has good stability by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It was reported that the reactivity of coke can be increased by adding minerals with a catalytic effect [14,15]. At present, researchers generally believe that the minerals that can improve coke reactivity mainly include transition metals [16,17], alkali earth metals [18,19], and alkali metals [20][21][22]. However, alkali earth metal and alkali metal minerals have been studied quite thoroughly as catalysts, and these two kinds of minerals could destroy the lining of a blast furnace and aggravate the degradation of coke during the process of blast furnace production [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the reactivity of coke can be increased by adding minerals with a catalytic effect [14,15]. At present, researchers generally believe that the minerals that can improve coke reactivity mainly include transition metals [16,17], alkali earth metals [18,19], and alkali metals [20][21][22]. However, alkali earth metal and alkali metal minerals have been studied quite thoroughly as catalysts, and these two kinds of minerals could destroy the lining of a blast furnace and aggravate the degradation of coke during the process of blast furnace production [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of coke can be enhanced by adding alkali metals (K, Na), [10][11][12] alkaline earth metals (Ca), [13,14] and transition metals (Zn, Fe). [15,16] However, alkali metals are harmful elements in the blast furnace.…”
Section: Introductionmentioning
confidence: 99%